PENERAPAN PASAL 374 KUHP JO PASAL 64 KUHP AYAT (1) DAN PROBLEMATIKA HUKUMAN YANG DIJATUHKAN OLEH HAKIM PIDANA DI PENGADILAN NEGERI SAMARINDA - Ismail Ismail (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Implementation of Article 374 of the Criminal Code jo article 64 paragraph (1) of the Criminal Code by the Panel of Judges in criminal cases. 15 / Pid.B / 2015 / PN.Smda is correct, but regarding the duration of the sentence handed down by the Panel of Judges regardless of the things that incriminate and alleviate the punishment imposed on perpetrators of criminal acts of embezzlement of property of the company conducted in succession . In relation to the criminal case where the defendant was sentenced for 5 (five) months, the author believes the sentence is very light. In relation to the problem of classification of criminal act of embezzlement as regulated and threatened with Article 374 of the Criminal Code jo article 64 paragraph (1) of the Criminal Code is a criminal act of embezzlement with a weighting. The legal consequences of the perpetrators of criminal act of embezzlement with the objections as regulated in Article 374 of the Criminal Code shall be imprisonment for a maximum of 5 (five) years. Whereas in the verdict of criminal case no. 15 / Pid.B / 2015 / PN.Smda as described above, against the perpetrator of criminal act of embezzlement of goods owned by the company which is done consecutively included in the classification of criminal act with the imprisonment for 5 (five) months imprisonment. Since such acts are included in the classification of criminal act of embezzlement with a denunciation, the action should have been severed with considerable punishment.